Long-Term changes in hot and cold extremes in Turkey - Acar, Zahide; Gönencgil, Barbaros; GÜMÜŞOĞLU, NEBİLE KORUCU (My University, 2018)
Extreme weathers are the leading cause of weather-related disasters all over the world. Many people lose their lives each year due to the triggering effect of cold or hot weather. The extreme days are generally defined as a period of several days of abnormally cold or hot weather. Increased frequency of these days could lead to death and disasters. This study analyzes the variability of minimum and maximum temperature defined anomalous temperature events. Daily minimum and maximum air temperature data from 156 weather stations in Turkey are analyzed to determine percentile threshold values (99th, 95th and 1st, 5th) at each station. Two statistical tests are applied to analyze trend in extreme values, namely Mann-Kendall trend analysis and cluster analysis. The Mann-.Kendall analysis demonstrates an increase in frequency of hot and extremely hot days, whereas cold and extremely cold days show a decreasing trend in Turkey. The extreme cold days have been the highest of the year 1972, 1983, 1992 and 1993, respectively. After 2005, extreme cold days begin to decrease. The frequency of extreme hot day has increased since 2000. Especially in 2010, it has been the warmest year in Turkey from the records of the stations during the study period.
Keywords: Turkey; Extremes; Cluster Analysis; Türkiye; Ekstremumlar; Küme Analizi